2020
DOI: 10.1097/mat.0000000000000933
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Outcomes in a Two-Center Cohort of Neonatal and Pediatric Patients Supported on Extracorporeal Membrane Oxygenation

Abstract: Contemporary studies of long-term outcomes in children supported on extracorporeal membrane oxygenation (ECMO) in the United States are limited. We enrolled 99 ECMO patients between July 2010 and June 2015 in a two-center prospective observational study that included neurologic and neuropsychologic evaluation at 6 and 12 months, using standardized outcome measures. Pre-ECMO, 20 (20%) had a pre-existing neurologic diagnosis, 40 (40%) had cardiac arrest, and 10 of 47 (21%) children with neuroimaging had acute ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 47 publications
2
53
0
Order By: Relevance
“…, one standard deviation below the reference population mean) or death up to 1 year after ECMO decannulation. 16…”
Section: Methodsmentioning
confidence: 99%
“…, one standard deviation below the reference population mean) or death up to 1 year after ECMO decannulation. 16…”
Section: Methodsmentioning
confidence: 99%
“…Broadly speaking, a child's adaptive behavior and functioning refer to the skills required to function well in one's environment and everyday life. Adaptive functioning in children who have suffered cardiac arrest has been assessed in studies using the Vineland Adaptive Behavior Scales-Second Edition (VABS-II; or the third edition, VABS-III) (20), a comprehensive parentreport measure that evaluates the domains of motor skills, communication, daily living, and socialization (21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Many studies have found impairments in adaptive functioning (22,24,25,(27)(28)(29), motor functioning (22,24,(27)(28)(29), communication (22,(27)(28)(29), and daily living skills (22,24,(27)(28)(29), when assessed at various time points, including 3 and 12 months following cardiac arrest.…”
Section: Adaptive Behavior and Functioningmentioning
confidence: 99%
“…For children supported with ECMO who develop brain injury, survival is greatly reduced. Survivors with brain injury also have poor developmental and functional outcomes [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%